Optimizing Diagnosis and Management of Dry Eye Disease: A Practical Framework for Hong Kong - Douglas Lam; Kelvin Chong; Kendrick Shih; Kelvin H. Wan; Arthur Cheng (Ophthalmology and Therapy)
Abstract Dry eye disease (DED) poses a significant and escalating public health challenge. Effective diagnosis is crucial for optimal management. However, current practices are complicated and time-consuming. This paper proposes a revised framework for diagnosing and treating in Hong Kong, explicitly tailored to the local healthcare context and incorporating insights from global consensus guidelines. The framework emphasizes a streamlined assessment strategy and prioritizes direct symptom-based questioning alongside objective tests. It also includes a simplified corneal staining grading scheme to reduce complexity, considering the limited consultation time available in Hong Kong. Furthermore, the framework clearly outlines the appropriate treatment options based on the disease’s severity and etiological cause(s) and focuses on the need for long-term management through follow-up or referrals. By addressing the multifaceted nature of DED and considering local healthcare constraints, this framework seeks to enhance patient outcomes through timely diagnosis and accurate assessment and treatment of DED.